Glycyrol attenuates colon injury via promotion of SQSTM1/p62 ubiquitination and autophagy by inhibiting the ubiquitin-specific protease USP8. (April 2023) - Lu, Shangyun; Xu, Jiali; Xu, Yang; Liu, Yang; Shi, Dongxing; Wang, Jia; Qiu, Fubin
Graphical abstract: Abstract: Maintaining the integrity and stability of the gut tract is essential for the health of the body. Autophagy is a promising target for balancing gut homeostasis, and numerous studies have focused on regulating autophagy to improve gut health. In this study, we found that glycyrol (GC), a representative coumarin compound isolated from Glycyrrhiza uralensis Fisch (used for medicine and food), can attenuate colon injury by activating autophagy. Specifically, we demonstrated that GC can act on ubiquitin-specific protease 8 (USP8), inhibit the interaction between SQSTM1/p62 and USP8, promote the ubiquitination of p62, and activate autophagy. Collectively, the findings of the present study suggest that GC is a novel and promising colon protector and deserves further investigation.